Motivation for COVID-19 Vaccination in Priority Occupational Groups: A Cross-Sectional Survey - Štěpánek, Ladislav; Janošíková, Magdaléna; Nakládalová, Marie; Ivanová, Kateřina; Macík, Jakub; Boriková, Alena; Vildová, Helena (International journal of environmental research and public health, 2021)
UNLABELLED: Due to the limited availability of COVID-19 vaccines, occupational groups with priority access were identified prior to vaccination. The study aimed to analyze motives for vaccination in these occupational groups. METHODS: Members of occupational groups, who were vaccinated at the vaccination center of University Hospital Olomouc before 30 April 2021, were asked to fill in an online questionnaire. RESULTS: A total of 3224 completed questionnaires were obtained from 1332 healthcare workers, 1257 school employees, 363 social service workers, 210 security force members, and 62 critical infrastructure workers. The most frequent motive for vaccination was the effort to protect family members (76.2%), the effort to prevent the spread of COVID-19 in one's profession (72.3%), followed by concerns about COVID-19 itself (49.1%) and exemptions from anti-epidemic measures (36.8%). Only for social services, the motive focused on one's profession was mentioned more often (75.2%) than the motive focused on the family (71.1%). At the level of detailed profession-oriented motives, a collegial effort of security force members to protect co-workers and not to endanger the workplace was dominant. CONCLUSIONS: The effort to prevent the spread of COVID-19 in the professional environment is a strong motive for vaccination, and strongest among social service workers.
Keywords: Health Personnel; průzkumy a dotazníky; SARS-CoV-2; vaccination; zdravotnický personál; Surveys and Questionnaires; průřezové studie; vakcinace; lidé; vakcíny proti COVID-19; COVID-19; Vaccination; motive; Cross-Sectional Studies; security forces; social service; motivace; occupational group; COVID-19 Vaccines; Motivation; Humans